Kompetensi Pedagogik Guru PAI dalam Menyusun Rencana Pelaksanaan Pembelajaran Berbasis Higher Order Thinking Skills - Siti Rahmah (Tadabbur: Jurnal Peradaban Islam, 2021)
This study aimed to determine the understanding of PAI teachers of SMA Negeri 1 Sigli on the concept of RPS based on HOTS, the pedagogical competence of PAI teachers at SMA Negeri 1 Sigli in preparing HOTS-based Learning Implementation Plans (RPP), and the factors that influence the competence of PAI teachers at SMA Negeri 1 Sigli in compiling HOTS-based RPP. To achieve these objectives, this study uses qualitative research methods. Data collection techniques are done through interviews and document analysis. The subjects of the study were 3 PAI teachers from SMA Negeri 1 Sigli, the Principal of SMA Negeri 1 Sigli, and the Deputy of Priancipal of SMA Negeri 1 Sigli in the curriculum. The results showed that: (1) In general PAI teachers who served in SMA Negeri 1 Sigli had a good understanding of the HOTS-based RPP concept, but one of them was still lacking, this was evident from his doubts in answering questions that the authors asked even there were some questions answered do not know. Besides that, it can also be seen from the discrepancy between the explanation submitted and the compiled lesson plan; (2) The results of the analysis of the Teacher's Learning Implementation Plan (RPP) indicate that the majority of PAI teachers of SMA Negeri 1 Sigli already have good competence in preparing HOTS-based RPPs, although they still need to be improved through trainings, while 1 other teacher does not yet have good competence, (3) Factors influencing pedagogical competence of PAI teachers in SMA Negeri 1 Sigli in preparing HOTS-based RPP consist of internal and external factors, each of which is differentiated into supporting and inhibiting factors. Supporting internal factors are self-motivation, while internal inhibiting factors are: (1) age, health and years of service and (2) ability to use media and IT-based tools. Supporting external factors are: (1) motivation and appreciation from the school; (2) participation in the district MGMP PAI forum, and (3) training, while the external factors inhibiting are: (1) limited infrastructure; and (2) the condition of students who tend to be passive.